An Investigation into Teaching Speaking Skills Using Communicative Activities to 11th Grade Students at Pham Phu Thu high school, Da Nang city - Văn Thị Thu Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study is aimed to examine the application of communicative activities in English Speaking Class for 11th grade students at Pham Phu Thu High School, Da Nang City and suggest ways to help improve English language learners’ speaking competence as well as enhance English language teachers’ speaking teaching efficiency